2021
DOI: 10.3390/s21165515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Abstraction Capabilities and Detection of Discomfort with a Newscaster Chatbot for Entertaining Elderly Users

Abstract: We recently proposed a novel intelligent newscaster chatbot for digital inclusion. Its controlled dialogue stages (consisting of sequences of questions that are generated with hybrid Natural Language Generation techniques based on the content) support entertaining personalisation, where user interest is estimated by analysing the sentiment of his/her answers. A differential feature of our approach is its automatic and transparent monitoring of the abstraction skills of the target users. In this work we improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Studies have revealed that chatbots perform better is they are specifically created for a certain domain or group ( De Arriba-Pérez et al, 2021 ). Chatbots can be used in domains such as e-commerce, business, marketing, communication, education, news, health, food, design, finance, entertainment, travel, or utilities, but not limited to them ( Liu et al, 2018 ; Adamopoulou and Moussiades, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have revealed that chatbots perform better is they are specifically created for a certain domain or group ( De Arriba-Pérez et al, 2021 ). Chatbots can be used in domains such as e-commerce, business, marketing, communication, education, news, health, food, design, finance, entertainment, travel, or utilities, but not limited to them ( Liu et al, 2018 ; Adamopoulou and Moussiades, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid mental issues, like depression and anxiety, they need to be engaged into the daily routine, to be stimulated and entertained ( Valtolina and Hu, 2021 ). Social interaction is considered a basic need for aging population in which solitude is one of the biggest issues ( De Arriba-Pérez et al, 2021 ). Like in a vicious circle, social isolation, rejection, or loneliness seems to have a paramount negative effect on the general and mental health of an individual.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application Reference Conversational agent AI-based multitasking conversational agent [23], [25], [27], [38], [44], [45], [53], [ [34], [39], [48], [52] Chatbot that manages information Chatbot in information management. [53] Chatbots con AI Chatbots with AI and cloud computing.…”
Section: Chatbot Typesmentioning
confidence: 99%